Self-Efficacy, Self-Awareness and Parental Involvement as Determinants of Goal Setting Among the Adolescent Youth - Makewa, Lazarus Ndiku; Ngila, Winnie Muthoni (IJRDO-Journal of Applied Science, 2015)
This study endeavored to test how self-efficacy, self-awareness and parental involvement affected goal setting among the youth. The study was descriptive and comparative in design in that subjects were measured once and that the variables were compared between subjects in terms of gender. Purposive sampling was done to obtain a sample with adolescents only; the sample consisted of 148 youths, making 31.092 % of respondents all aging between 13 and 24 years. A questionnaire was constructed to test on self-efficacy, self-awareness and parental involvement as determinants of goal setting among the youth. The questionnaire had a reliability of 0.767. Mean ratings of the variables were compared in analysis of the descriptive information of the variables. Results of frequencies and mean comparisons were used to answer the first research question. ANOVA was done to determine whether there was a significant difference in the determinants of goal setting among the youth in terms of gender so as to answer the second question. To answer question three, Pearson correlation coefficient was determined. The results indicate that respondents bear perceived self-efficacy that can influence them positively in goal setting. While self-efficacy and self-awareness emanate from within an individual, parental involvement is an external factor. Nevertheless, among the three variables, it has the highest mean rating as a factor that influences goal setting among the adolescent youths. The study established that there is no significant difference in the determinants of goal setting between male and female youths. Another moderately positive relationship is observed between self-efficacy and parental involvement in goal setting among the youth.